2017
DOI: 10.1210/en.2017-00429
|View full text |Cite
|
Sign up to set email alerts
|

The Two Populations of Kisspeptin Neurons Are Involved in the Ram-Induced LH Pulsatile Secretion and LH Surge in Anestrous Ewes

Abstract: Exposure to a ram during spring stimulates luteinizing hormone (LH) secretion and can induce ovulation in sexually quiescent ewes ("ram effect"). Kisspeptin (Kiss) present in the arcuate nucleus (ARC) and the preoptic area (POA) is a potent stimulators of LH secretion. Our aim was to investigate whether Kiss neurons mediate the increase in LH secretion during the ram effect. With double immunofluorescent detection, we identified Kiss neurons (Kiss IR) activated (Fos IR) by exposure to a ram for 2 hours (M2) or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 58 publications
1
13
0
Order By: Relevance
“…Our study showed a response potentially within 2 hours with mean LH significantly greater in supplemented animals at this time. Importantly, supplemented feed effects in male sheep are far more subtle and variable between animals -consistent with our relatively small changes in KNDy neurons -than other stimuli, such as the ram effect (De Bond et al 2013;Fabre-Nys et al 2017). This variability is evident in our kisspeptin-fos data, which only represents a single point in time and unfortunately cannot be directed paired to the overall LH activity during each period.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Our study showed a response potentially within 2 hours with mean LH significantly greater in supplemented animals at this time. Importantly, supplemented feed effects in male sheep are far more subtle and variable between animals -consistent with our relatively small changes in KNDy neurons -than other stimuli, such as the ram effect (De Bond et al 2013;Fabre-Nys et al 2017). This variability is evident in our kisspeptin-fos data, which only represents a single point in time and unfortunately cannot be directed paired to the overall LH activity during each period.…”
Section: Discussionsupporting
confidence: 70%
“…Evidence further suggests that kisspeptin neurons may be the 'missing link' between HPG activity and nutritional cues. KNDy neurons are known to mediate environmental effects on reproductionthey are involved in the 'ram effect', a phenomenon where ewes show a surge in HPG activity when presented with a novel ram (De Bond et al 2013;Fabre-Nys et al 2017). Importantly, kisspeptin also seems to be involved in responses to nutritional signals, particularly in rodents, where several lines of evidence have been published: i) fasting decreases Kiss mRNA and central administration of kisspeptin reverses fasting-induced inhibition of GnRH secretion (Castellano et al 2005); ii) kisspeptin neurons apposite to GnRH neurons possess insulin, leptin and ghrelin receptors (Qiu et al 2011;Cravo et al 2013;Frazao et al 2014;Qiu et al 2015); iii) leptin-deficient ob/ob mice have lower levels of Kiss1 mRNA in the ARC, compared to wild-type controls, and the peripheral administration of leptin reduces this effect (Smith et al 2006); iv) kisspeptin also interacts with the insulin signalling pathway in the hypothalamus, as evidenced by diabetic rats having diminished expression of Kiss1 mRNA, an effect that can be reversed with insulin therapy (Castellano et al 2006); and v) impairment of kisspeptin signalling decreases metabolism and increases obesity and glucose intolerance (Tolson et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Kisspeptin and the amygdala have been shown to be critically involved in the integration of olfactory cues with the promotion of sexual behaviour. Lesioning of the MePD results in a diminution of sexual partner preference in rodents and, in the “ram effect”, where the introduction of a sexually active ram can overcome reproductive inactivity in anoestrous ewes, the resurgence of functional LH pulsatility coincides with an increase in Kiss1 neurone activity (FOS) in the ARC, POA and MeA . Our previous study using pharmacological activation of MePD Kiss1 neurones with the DREADD (Designer Receptors Exclusively Activated by Designer Drugs) methodology built upon previous understanding of the facilitatory role of the MePD in sexual behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…Since the discovery of the link between mutations in the human gpr54 and isolated hypogonadotropic hypogonadism (de Roux et al, 2003 ; de Roux, 2006 ), the kisspeptins have become a key to the central dogma of neuroendocrine regulation of mammalian reproduction (Figure 1 ). Critical work in several mammalian species has now established that specific kisspeptin neuronal populations directly control Gnrh neurons to regulate Lh release (Clarkson and Herbison, 2009 ; Fabre-Nys et al, 2017 ). In vivo and in vitro studies in fish showed that exogenous kisspeptin peptides could variably enhance Lh release, depending on form and species (Espigares et al, 2015 ; Zmora et al, 2015 ).…”
Section: Kisspeptinergic Systems Are Not Essential In Small Model Telmentioning
confidence: 99%